Fairness in Complaint Handling and Its Theoretical Implications for Service Recovery: Evidence from E-Commerce Customers in Denmark - Tengku Ahmad Helmi; Endi Rekarti; Sri Yusriani; Prasetyo Harisandi (Dinasti International Journal of Education Management And Social Science, 2025)
This study explores the relationship between customer complaint management and its impact on customer satisfaction and subsequent purchasing behavior in Denmark. We developed a refined complaint handling model, emphasizing fairness across three key dimensions: distributive justice, procedural justice, and interactional justice. These dimensions are hypothesized to significantly influence customer satisfaction, which, in turn, affects purchasing intentions. Using online surveys, we assessed customer perceptions of complaint handling, focusing on these critical dimensions. Data collected from 250 Danish consumers, each having filed at least one complaint, were analyzed using the Partial Least Squares (PLS) approach. The analysis revealed a significant link between effective complaint management and enhanced customer satisfaction, which notably influences purchasing intentions. Initially, our model did not demonstrate a direct impact on purchasing behaviors, leading to its refinement. The revised model indicates that customer satisfaction with the resolution process predominantly dictates future purchasing decisions, while dissatisfaction with the complaint handling does not directly affect future purchases. This research is distinguished by its innovative complaint handling model and the application of PLS methodology, providing deeper insights into the dynamic interactions between studied variables. The focused and highly relevant sample underscores the study's significance, particularly in the e-commerce sector.